(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: Thrombolytic therapy with streptokinase is the mainstay of pharmacological treatment in acute myocardial infarction in Pakistan. Retinal hemorrhage is a common complication of streptokinase-induced thrombolysis and is often overlooked which can lead to permanent vision loss. Therefore, this study was carried out to determine the frequency of retinal hemorrhage after thrombolysis with streptokinase in patients presenting with ST-elevation myocardial infarction (STEMI). Patients and methods: It was an observational, cross-sectional study conducted at the Emergency Department of Mayo Hospital Lahore from 11-08-2015 to 10-02-2016. The patients underwent injection of streptokinase (1.5 million U) intravenously over 60 min and intravenous heparin 5,000 U bolus followed by 1,000 U/hour. Then patients were followed up for 24 hours followed by the ophthalmoscopy to confirm the presence of retinal hemorrhage. The data were entered and analyzed using SPSS version 20. Results: A total of 130 patients were included in this study. The mean age of patients was 62±9.86 years. The male to female ratio was 1.6:1. The retinal hemorrhage was present in 17 (13.08%) patients. About 80 (61.5%) were diabetics and 96 (73.8%) were hypertensive. Stratified variables like age, gender, hypertension, and diabetes were not found associated with retinal hemorrhage (p-value ≥0.05). Conclusion: Retinal hemorrhage was found in 13.08% after streptokinase injection in patients presenting with STEMI. Although the association was statistically insignificant but still the proportion of retinal hemorrhage was substantially high in these patients. This higher percentage demands vigilant monitoring with the drug for timely diagnosis of this ignored complication which latter can be proved hazardous to the vision.